A bibliometric analysis of halal cosmetics consumer behaviour in Indonesia - Pradana, Mahir; Elisa, Hanifah Putri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The increasing number of halal cosmetics companies in Indonesia meets consumer demand for products that comply with halal standards. Therefore, this study aims to examine the viewpoints of academics towards the literature on halal cosmetics. This research uses bibliometric analysis to examine the results and then visualize the results. This research uses the Google Scholar database, Microsoft Excel for statistical analysis, and VOSviewer, a network map generator program, for bibliometric analysis. The conclusion of this study is that in the coming years, the halal cosmetics market in Indonesia is expected to expand significantly. Increasing consumer knowledge of halal cosmetics and their advantages is the driving force. The demand for halal products is also met by the increasing number of businesses in Indonesia that sell halal cosmetics. These businesses can concentrate on creating cosmetics that are not only halal but also safe and healthy for the skin by using natural components.